The role of PBL in improving physics students’ creative thinking and its imprint on gender. - Elnetthra Folly Eldy (2013)
Creativity is one of the components in thinking skills that realized as one of a critical feature for a developing industrial country like Malaysia. The main objective of this paper is to provide details of students? score on several criteria?s of creative thinking who was previously done from YanPiaw Creative-Critical test analysis and in addition of that also to present an evidence to support the previous study on the relationship between creativity and gender. The subjects of this study were 28 Physics with Electronics undergraduate students exposed to problem-based learning (PBL) for one semester (i.e., 14 weeks) during Semester 2, Session 2012/2013 academic year. The study took place at School of Science & Technology, University Malaysia Sabah. The results and comparison of the findings in this study with previous study was present, also accompanying by proper discussion.